Understanding Whistleblowing Intention Among Public Sector Employees in the Northern Region of Malaysia: Does Gender Matter? - Zul Muhammad Zairi; Abdullah Muhammad Syukri; Awang Tuah Siti Normah; Zainudin Zatil Aqmar; Aziz Anidah (Information Management and Business Review, 2023)
The objective of this study is to determine the factors influencing whistleblowing intention among public sector employees. This study utilized the Theory of Prosocial Behavior which includes contextual determinants (policy and procedure, training, responsiveness of management, reporting channel, financial reward, seriousness level of wrongdoing) and individual determinants (knowledge, trust) as independent variables while whistle blowing intention is the dependent variable. Additionally, this study also includes gender as a moderating variable in the relationship between the contextual and individual determinants toward whistleblowing intention. The data was collected from 123 public sector employees in the northern region of Malaysia (Perlis, Kedah, Penang) from various ministries via an online survey questionnaire and analyzed using SmartPLS. This study found that there is a significant relationship between all independent variables and whistleblowing intention, except for the responsiveness of management. Additionally, gender was found to be significant in the relationship between several independent variables and whistleblowing intention.